The development of narrative skills of Thai children - Sorabud – Rungrojsuwan (Penerbit Universiti Kebangsaan Malaysia, 2023)
A fundamental goal of the study of language development is to establish a developmental standard for typically developing children (Bates et al., 1995; Fenson et al., 1994; Fenson et al., 2003; Ingram, 1989; Rungrojsuwan, 2003; Salleh et al., 2020). As one of the most familiar interpersonal practices among children in all cultures, traditional narrative discourses have been employed as resources for the study of language development (Berman & Slobin, 1994; Bliss et al., 1998; Justice et al., 2010; Labov & Waletzky, 1967; Piyapasuntra, 2009; Ratitamkul, 2010; Rungrojsuwan, 2019a; Rungrojsuwan, 2019b). Using the Thai narrative Corpus (Zlatev & Yangklang, 2001), the present study aims to examine the normality of development for Thai children’s narrative skills from preschool (3-4 years old) to school-age (9-11 years old) in three aspects: continuity of events, elaboration of details, and imagination of the narrators. The onset of narrative development starts in preschool, when the children show limited and relatively simple linguistic structures to describe the story. By primary-school, their linguistic structures were more complex, rich with information, including background information, and story evaluation. The study proposes a sequential order of linguistic development for typically developing Thai children.